Design Principles and Calculation Criteria for Skewed Notches in PM Motors - Siwei Ji; Yukai Li; Huanyu Ou; Wenlong Tian (Energies, 2023)
The stator structure is one of the main factors affecting the electromagnetic performance of permanent magnet (PM) motors. In this paper, an in-depth study and analysis of how to reduce the cogging torque is carried out from the perspective of the stator structure. According to the theory of cogging torque synthesis, this paper presents a unified calculation formula for different PM motor skewed notch designs. This theory is verified with a 20-pole, 60-slot motor and a 20-pole, 24-slot motor, respectively. The formula worked out proved to be highly applicable. The formula is intended to address how to quickly obtain key data (skew angle, notch depth) in a skewed notch study.